Towards devising an effective and reliable means of fish detection and classification through the exploration of various deep learning algorithms - Farhan, Rafid; Rahman, Ninad Abdur; Ahsan, Syeda Sara Ummy (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.